WORSHOPS ON ARTISTIC PRACTICES AS LEARNING PLACES: WHAT DOES IT MEAN? - Beatriz Sancovschi; Jerusa Machado Rocha (Universidade do Estado do Rio de Janeiro (UERJ), 2023)
The article aims to reflect on the issue of learning, based on artistic practices workshops, held, between 2014 and 2019, with elementary school students from a school for the visually impaired in Rio de Janeiro. The premise was that this was a learning space, but what does this mean? We will follow the tracks of Deleuze, Kastrup and Gallo as a starting point and expand from there. Those theorists advocate non-representational learning. Learning is not restricted to the passage from not knowing to knowing, but rather involves sensitivity, a condition for transforming oneself and the world. So the problem is how to become sensitive? We will proceed by producing a dialogue with the enactive approach to cognition and with a rereading of the concept of Proximal Development Zone in order to propose a Zone of Sensitivity.